Individual Centric Framework for Quantifiable Attainment of CareerAspirations: An Indian Perspective - Kumari, Madhuri; Hasteer, Nitasha (Journal of Engineering Education Transformations, 2018)
Focus of the Indian higher education system has been more job centric, thereby losing the value of learning. Limited learning eventually results into less employability. There has been a significant drop in the number of employable fresh graduates. Industry also claims that lot of resources are being utilized to convert raw resources into usable workforce. The various initiatives of the Indian government like Skill India clearly indicates that the need of the hour is therefore to restructure the academic learning process. The solution to the challenges being faced by the current learning process of the Indian higher education system is to adopt an individual centric outcome approach.This paper proposes an individual centric outcome based education (i-OBE) framework which is modified version of outcome based framework. This framework aims to enhance the outcome based education by integrating an individual centric approach throughout the execution of an academic programme in a stipulated time frame. The paper discusses the application of the proposed framework to the four-year undergraduate engineering degree. The framework efficacy has been tested by implementing it partially through a career assessment tool on 1215 subjects. Our findings reveal that the individual centric outcome approach results in quantifiable attainment of career aspirations as against traditional outcome based approach.